GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 11340999 species occurrences available in GBIF matching the query: TaxonKey: Plantae or Liliopsida BasisOfRecord: Observation. The dataset includes 11340999 records from 161 constituent datasets: 14894 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 14765 records from OEH Atlas of NSW Wildlife. 5774 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 236 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 56184 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 6 records from New records in vascular plants alien to Kyrgyzstan. 104 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1358 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 893 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 2 records from Highland Biological Recording Group - HBRG Insects Dataset. 13 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 314 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 46536 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 678 records from BioFokus. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 535 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 9086 records from Flora of Słowiński National Park, Poland. 2865 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 1516 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1401 records from Plant observations from Białowieża National Park. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 3283 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 23155 records from Australia's Virtual Herbarium. 154344 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 3 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 4858 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 16 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 24 records from CONN. 3 records from Upper Silesian Museum, Bird Observations. 1820 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 40 records from Countryside Council for Wales - Shad Monitoring data. 1855 records from corrego_fazendinha-gallery-forest_v2. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 76 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 10666 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 34 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 49781 records from Continuous Plankton Recorder Dataset (SAHFOS). 250427 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 565 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 54400 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 14108 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 3 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 817 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 10148 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 4851 records from National Trust - Hatfield Forest species data held by The National Trust.. 80273 records from Scottish Natural Heritage - Standing Waters Database. 103 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 307 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 20 records from New records for Albania based on taxa from the Prespa National Park. 9 records from Bats of Poland. 420573 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 4813 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3005 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 105522 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 5291 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1 records from Sistemática del género Polianthes L (Agavaceae). 368 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 83 records from Flora de macroalgas del litoral oaxaqueño. 47523 records from NatureServe Network Species Occurrence Data. 78 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 237 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 131 records from Flora de las Barrancas del Cobre. 1016 records from Inventario nacional de especies vegetales y animales de uso artesanal. 110 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 17 records from Conocimiento de la macroflora marina de interés económico de las Costas de Yucatán. 683 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 1 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 2 records from Inventario de la biota terrestre (florístico) del parque nacional Isla Isabel. 12 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 4438 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 3 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 21263 records from The Himalayan Uplands Plant database (HUP Version 1). 3761 records from Mountain Invasion Research Network (MIREN) survey. 30 records from CABI Bioscience Fungus Collection. 292665 records from Observational database of Icelandic plants. 4279 records from Universitat de Girona: HGI-Cormophyta. 1 records from HMAP-History pf Marine Animal Populations (CoML). 6949 records from NODC WOD01 Plankton Database. 1 records from SeamountsOnline (seamount biota) (CoML). 6 records from HerbarioHerrerense. 84 records from Natural Geography In Shore Areas (NaGISA) Dataset. 72 records from Scottish Natural Heritage - Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 177 records from BioMar (EurOBIS). 8009 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 4 records from MICROBIS database. 2 records from Phragmites of Canada. 7939 records from Botany registration database by Danish botanists. 46 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 2 records from AlgaTerraMovies. 355 records from GEO Biodiversity Day. 4675043 records from Observations du Conservatoire botanique national du Bassin parisien.. 252389 records from Israel Nature and Parks Authority. 42 records from The Erysiphales Collection at the Botanische Staatssammlung München. 422 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 230 records from AWI-Herbarium Marine Macroalgae. 133 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 78 records from Electron Micrograph Database - Marine Specimens. 182 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 309 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 5060 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 259575 records from Staffordshire Ecological Record - SER Site-based Surveys. 2251 records from Plant Systematics Laboratory, Ajou University, Korea. 57 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 2 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 6 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 5 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 71894 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 62 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1935 records from Spring bryophyte flora of Salpausselkä (Ulvinen 1955 & Juutinen 2006). 3 records from Amphibian observations from Nida Valley. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 22 records from British Lichen Society - BLS Lichen Database: England. 1 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 6670 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 741 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 195727 records from National vegetation diversity inventory and mapping plan. 9 records from British Lichen Society - BLS Lichen Database: Wales. 1004 records from National Trust - Sutton Hoo species data held by The National Trust.. 1551 records from fundo. 3426 records from National Trust - Ickworth species data held by The National Trust.. 349 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 926 records from John Muir Trust - Knoydart Bryophytes, 1990. 21861 records from Staffordshire Ecological Record - SER Species-based Surveys. 17228 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 617 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 619 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 354 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2864 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 558 records from Countryside Council for Wales - Freshwater Site Visits. 80451 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 2546 records from Nature Locator - PlantTracker data from 2012 onwards. 1 records from Herbarium - Las Cruces Biological Station. 401 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 1250 records from Plant Observation Records of Japan. 537 records from National Trust - Heigham Holmes species data held by The National Trust. 642 records from Thames Valley Environmental Records Centre - English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 52420 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 684511 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1494 records from Countryside Council for Wales - Stoneworts in Wales. 843 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 18166 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 2418781 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 14 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 376 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 486 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 705 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 732170 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 44554 records from Flora of the Stołowe Mts.. 17 records from UCDavis - Western USA - Monarch Butterflies - 1892-2005. 1 records from Countryside Council for Wales - Bullhead Survey Data in Wales. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences